Tyrosine kinase inhibitor‐induced vasculopathy in clear cell renal cell carcinoma: an unrecognized antitumour mechanism. Issue 4 (26th November 2013) - Tsuzuki, Toyonori; Sassa, Naoto; Shimoyama, Yoshie; Morikawa, Takamitsu; Shiroki, Ryoichi; Kuroda, Makoto; Fukatsu, Akitoshi; Kuwahara, Kyoko; Yoshino, Yasushi; Hattori, Ryohei; Gotoh, Momokazu
<x xml:space="preserve">Abstract</x> Aims To evaluate the pathological features of clear cell renal cell carcinoma (CCRCC) treated with tyrosine kinase inhibitors (TKIs), and to elucidate the mechanism of action of TKIs. Methods and results Twenty cases of CCRCC treated with TKIs (sorafenib or sunitinib) were retrospectively analysed: 16 were patients who had undergone radical nephrectomy after neoadjuvant TKI therapy, and four were autopsy cases of patients who received TKI treatment. All tumours had two distinct regions: one characterized by necrosis and/or degeneration, indicating antitumour activity; and the other characterized by no or few pathological changes, indicating the absence of antitumour activity. Vasculopathy of tumour vessels was observed in or adjacent to the necrotic or degenerative areas; a decreased density of endothelial cells was noted in the tumour vessels. Few or no changes of vasculopathy were observed in tumour vessels in the other CCRCC areas, indicating the absence or low levels of antitumour activity. Conclusions This is the first pathological report of vasculopathy in TKI‐treated CCRCC cases. Our data suggest that TKIs initially induce vasculopathy in tumour vessels, and consequently cause reduction or diminution of blood supply to the CCRCCs, resulting in antitumour activity characterized by necrosis and hyalinization.